Expression of maspin in benign and malignant salivary gland tumors: An immunohistochemical study - V Reshma; Kavita Rao; N S Priya; H S Umadevi; T Smitha; H S Sheethal (Indian Journal of Dental Research, 2014)
Context: Maspin is a novel serine protease inhibitor (serpin) with multifaceted tumor-suppressive activities. It was originally identified in normal human breast myoepithelial cells and shows variable expression in different types of cancer cells. Maspin displays anti-metastatic properties in mammary and prostate cancer. Its expression is maintained during ovarian, lung and pancreatic carcinogenesis, indicating that Maspin regulated metastatic potential is tissue specific. Thus, it is possible that Maspin participates in salivary gland tumor biology as well. In this study, expression pattern of maspin in benign and malignant salivary gland tumors is analyzed, to understand the biological behavior of salivary gland tumors with respect to maspin expression. Aims and Objectives: The aim of this study was to demonstrate, record, and correlate the expression pattern of maspin in benign and malignant salivary gland tumors. Settings and Design: A retrospective study of maspin expression in 30 diagnosed cases of benign and malignant salivary gland tumors retrieved from archives of our department. Materials and Methods: Anti-maspin antibody and horseradish peroxidase detection system. Statistical Analysis: Descriptive statistical analysis and Chi-square/Fisher Exact test. Results: Intense expression with P < 0.001 is associated with benign tumors, nuclear staining with P < 0.001 is significantly associated with benign tumors and cytoplasmic staining with P = 0.020 is associated with malignant tumors. Conclusion: Intensity of expression is more in benign tumors when compared with malignant tumors. The benign tumors showed both nuclear and cytoplasmic expression. Some malignant tumors did express maspin, but mainly in the cytoplasm.